A modified specimen holder for cone calorimeter testing of composite materials to reduce influence from specimen edges. (16th February 2021) - Sandinge, Anna; Blomqvist, Per; Rahm, Michael
SUMMARY: ISO 5660‐1 specifies the cone calorimeter method for characterizing the ignition and surface burning behavior of materials. The specimen is irradiated through a square opening in the frame of the specimen holder. The frame is intended to protect the edges of the specimen from irradiation but covers the edges with only a few mm. In tests with products such as composite laminates and sandwich wall panels, the production of pyrolysis gases from the edges and, in many cases, burning have been observed. Early contribution from the edges in the test is not representative for surface burning. A modified specimen holder was developed with a larger specimen size to allow better protection of the edges. The opening for exposure to irradiance of the retainer frame is circular and of the same area as that of the original frame. The distance between the exposed surface and the specimen edges is larger in order to prevent early exposure of edges. Tests using the standard specimen holder resulted in pyrolysis and burning from edges that took place outside of the specimen holder. Comparative tests using the modified specimen holder showed that it prevented the exposure and pyrolysis from edges for an extended time. However, the influence on ignition time and peak heat release due to the increased size of the modified specimen holder has not been characterized fully, and test results should not be used for direct comparison with those of the standard holder.